Music and the creative spirit : innovators in jazz, improvisation, and the avant garde - Peterson, Lloyd, 1955- (Studies in jazz, 2006)
"Music and the Creative Spirit: Innovators in Jazz, Improvisation, and the Avant Garde aims to give today's brightest music innovators recognition and respect, celebrating their work and creativity. Through personal interviews, artists offer clear, frank discussions about music, creativity, work, society, culture, current events, and more."